Discourse Network Analysis: Emission Reduction Commitments in Carbon Trading Policies - Widiastiana Vista Wijaya; Siti Zulzilah; Shilvy Andini Sunarto; Citra Puspa Maulidina (Jurnal Sosial Humaniora dan Pendidikan, 2025)
This research examines the news discourse on carbon trading policy through carbon exchange on Kompas.com online media. The efforts made by Indonesia to reduce greenhouse gas (GHG) emissions by organizing carbon trading through carbon exchanges. Referring to the network context of policy implementation proposed by Barry Markovsky, the dimensions emphasized in the network exchange theory (NET) perspective are the structure and relations of actors. In line with this, Paul A. Sabatier said the advocacy coalition framework (ACF) focuses on actors each having a position on an issue. Based on the discourse of the two theories, this research has an argument that the process of making public policy from the issue of carbon trading to the implementation of the policy in technical regulations on the Otoraritas Jasa Keuangan Regulation Number 14 of 2023 concerning Carbon Trading through Carbon Exchange (POJK 14/2023) with Circular Letter of the Otoritas Jasa Keuangan Number 12/SEOJK.04/2023 concerning Procedures for Implementing Carbon Trading through Carbon Exchange.